TORAKOCHIRURGIAChylothorax as a problem in thoracic and cardiac surgery. Part I. Diagnostics and symptoms - Rokicki, Wojciech; Rokicki, Marek; Filipowski, Marek; Wojtacha, Jacek; Zygo, Agnieszka (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Lymphorrhoea is a rare disease evaluated in selected groups of patients in the 0.5-2.0%. The primary cause is thoracic duct obstruction by mediastinal tumour and/or damage to its walls during the treatment of toraco-cardiac surgery. Lymphorrhoea not treated in a short period of time can lead to hypovolaemia, hypotension, hypoproteinaemia, emaciation, lowered immunity, shock and even death. As presented in the publication, the authors discuss the contemporary principles of diagnosis and treatment of diseases, both conservative and surgical.